The Influence of Personnel Management and Servant Leadership on Teacher Discipline - Suprihatin Suprihatin; Yudithia Dian Putra; Ainur Rofiq; Loso Judijanto; Etin Indrayani (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
This study aims to delve into the existing relationship between personnel management, the concept of servant leadership, and the level of personnel discipline in educational institutions. A quantitative research method was chosen as the primary approach to collect and analyze data to obtain a strong understanding of these dynamics. Respondents involved in this study are educational personnel from various backgrounds and educational levels, providing a broader representation of the education population. In the data collection process, validated research instruments with high reliability were used to measure key variables involved, such as leadership styles, personnel management practices, and discipline levels. Careful statistical steps were applied in data analysis, including regression techniques, to identify the strength of the influence of personnel management and servant leadership on the level of personnel discipline in education. From the results of this analysis, it is expected that significant patterns and correlations between the examined variables will be revealed. The findings of this research are expected to provide new insights into the factors underlying discipline levels in educational institutions. The practical implications of this study will be valuable for managers and stakeholders in the field of education, aiding them in designing more effective management strategies to enhance personnel discipline, which in turn can positively impact the overall quality of education. Thus, this study not only fills gaps in the academic literature on educational management and leadership but also makes a significant contribution in practical contexts by offering a framework that can be applied to enhance the quality of education through improvisation personnel discipline.